Economic Development Implications of the Venezuelan Migrant Crisis Trinidad and Tobago and the Caribbean Community - Hosein, Roger; Gonzales, Anthony; Tewarie, Bhoendradatt; Gookool-Bosland, Rebecca (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book analyzes the ways in which the Venezuelan immigrant community is making an impact on the social and economic dynamic of small economies. This publication addresses some of the main economic development conversations on trade, labor, and fiscal implications of immigration. This book attempts to collate and unpack some of the relevant theoretical frameworks which provide a basis for policymakers and other key decision-makers. In this regard, the links between immigration and economic development is discussed with a focus on Trinidad and Tobago as a representative case within the Caribbean community. Roger Hosein is a Senior Lecturer in the Department of Economics at the University of the West Indies, St. Augustine, Trinidad and Tobago. He is also the coordinator of the Trade and Economic Development Unit (TEDU) a research cluster within the Department of Economics. Anthony Gonzales is the former Director of the Institute of International Relations at the University of the West Indies, St. Augustine, Trinidad and Tobago. Bhoendradatt Tewarie is the former Vice Chancellor of the University of the West Indies, St. Augustine, Trinidad and Tobago. Rebecca Gookool-Bosland is a Lecturer in the Department of Economics at the University of the West Indies, St. Augustine, Trinidad and Tobago. .
Chapter 1: The Venezuelan Migration Crisis: Evolution and Prospects -- Chapter 2: Venezuelan Migrants: A Comparative Look at T&T and Other Latin American and Caribbean Countries -- Chapter 3: Labour Market Impact of Immigration -- Chapter 4: Trade Impact of Immigration -- Chapter 5: Fiscal impact of immigration -- Chapter 6: A Regional, Hemispheric or Global Approach to the Venezuelan Immigrant Crisis? -- Chapter 7: Establish a Zone of Peace, Prosperity and Sustainable Development in the Americas. .
Keywords: Development economics; Emigration and immigration; Development Economics; Human Migration